Pharmacovigilance Knowledge and Perceptions Among Pharmacy, Medical and Nurse Students in University of Duhok - B. Allela, Omer Qutaiba; Elkalmi, Ramadan M.; Saleem Salih, Avan; Yousif, Diana Yaqo; Ali, Hala Wazir; Shammo, Narmin Oraha (Journal of Pharmacy Practice and Community Medicine)
Objective: To assess pharmacy, medical and nurse students’ knowledge of and perceptions about pharmacovigilance and reporting of adverse drug reactions (ADRs) at University of Duhok (UOD). Methods: A cross-sectional study was conducted from November 1, 2017, through January 1, 2018 using a validated self-administered questionnaire delivered to a sample of 202 students at Colleges in UOD. Results: About 42% of students indicated that they had taken courses on the concept of pharmacovigilance during their current curriculum. The mean score for knowledge about pharmacovigilance and ADR reporting was 6.98. There was a significant difference in the mean scores for knowledge about pharmacovigilance across the Colleges. About 38.6% of the respondents believed that students are competent and capable of reporting ADRs during their clerkships. The majority (67.6%) of respondents perceived that students should be taught how to report ADRs. Conclusion: The results of this study demonstrate that the majority of students in public universities have insufficient knowledge about pharmacovigilance and ADR reporting.
Keywords: Pharmacovigilance; Knowledge; Perception; Iraq